Meta-Analysis and Systematic Review of Phenotypic and Genotypic Antimicrobial Resistance and Virulence Factors in Vibrio parahaemolyticus Isolated from Shrimp - Varangkana Thaotumpitak; Justice Opare Odoi; Saran Anuntawirun; Saharuetai Jeamsripong (MDPI AG, 2024)
This systematic review and meta-analysis investigates the prevalence of Vibrio parahaemolyticus, its virulence factors, antimicrobial resistance (AMR), and its resistance determinants in shrimp. This study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, to identify and select relevant peer-reviewed articles published between January 2020 and December 2022. The search strategy involved multiple online databases, including Google Scholar, PubMed, ScienceDirect, and Scopus. The inclusion criteria focused on studies that examined V. parahaemolyticus prevalence, virulence factors, and AMR in shrimp from farms to retail outlets. A total of 32 studies were analyzed, revealing a pooled estimate prevalence of V. parahaemolyticus in shrimp at 46.0%, with significant heterogeneity observed. Subgroup analysis highlighted varying prevalence rates across continents, emphasizing the need for further investigation. Virulence factor analysis identified thermostable direct hemolysin (tdh) and tdh-related hemolysin (trh) as the most common. Phenotypic AMR analysis indicated notable resistance to glycopeptides, nitrofurans, and beta-lactams. However, the correlation between antimicrobial usage in shrimp farming and observed resistance patterns was inconclusive. Funnel plots suggested potential publication bias, indicating a need for cautious interpretation of findings. This study underscores the urgency of coordinated efforts to address AMR in V. parahaemolyticus to safeguard public health and to ensure sustainable aquaculture practices.